Association between artificially sweetened beverages consumption and changes in body mass index among children - Muhammad Bilal Arshad; Muhammad Usman Sheikh; Muhammad Afzal; Aneela Amjad; Shahzeb Patoli; Muhammad Behzad Salahuddin (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Poor food quality and choices are a major concern in the modern life style and increased consumption of sweetened and artificially sweetened beverages have been implicated as contributing factors for obesity. The objective of this study is to determine the association between the consumption of artificially sweetened beverages and changes in body mass index among children. METHODOLOGY: Data on the consumption of artificially sweetened beverages consumption and BMI for 13,287 children was analyzed for exposure and outcome from Millennium Cohort Study (MCS). The association between frequency of ASB consumption and BMI was quantified using demographics and linear regression analysis. The linear regression analysis was done adjusting demographic, socioeconomic variables and confounding factors of frequency of physical activity. Regression analysis was conducted using survey weights to account for the complex sampling design. RESULTS: Adjusted linear regression for demographical and socioeconomic variables showed that more frequent consumption of ASB was associated with a significant increase in BMI. As the frequency of ASB increased, BMI significantly increased by 0.69-1.06 units in categories (p<0.01). Regression analysis adjusted for frequency of physical activity also showed an increase of BMI by 0.36 units (p<0.01) with the highest frequency of ASB consumption. CONCLUSION: Higher consumption of artificially sweetened beverages causes an increase in BMI among UK children.